Pengendalian Kimia dan Resistensi Vektor Anopheles Dewasa pada Kawasan Endemis Malaria di Dunia - Musfirah, Musfirah (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2017)
Background: Various methods of malaria vector control has been done. Insecticides which using repeatedly impact new problems for the emergence of vector resistance. Hence, optimizationÂ  about active ingredientÂ  in the insecticideÂ  productÂ  should take noticeÂ  toÂ  the developmentÂ  ofÂ  insecticide resistanceÂ  mechanisms forÂ  malariaÂ  vectors. Literature review whichÂ  assess and discussÂ  adult Anopheles sp resistanceÂ  forÂ  chemical control programmeÂ  wereÂ  still limited to certain insecticides. The aimÂ  ofÂ  thisÂ  literature review isÂ  collecting andÂ  findingsÂ  evidence has been producedÂ  by researchers whichÂ  associatedÂ  withÂ  chemical control ofÂ  vectorÂ  andÂ Â  varietyÂ  ofÂ  adultÂ  Anopheles resistanceÂ  asÂ  aÂ  strategyÂ  to eradicate malaria endemic cases. Method: This literature review prepared by systematic review methods.Google database is used as the primary source of search with keyword "adult Anopheles", "resistance", insecticideâ, and chemical control".Â  InclusionÂ  andÂ  exclusion criteriaÂ  appliedÂ  toÂ  selectÂ  journalsÂ  thatÂ  areÂ  relevant ofÂ  this literature reviewâs topic. Collected 41 articles and 10 articles are matched with inclusion criteria. Results: Chemical control obtain cause Anopheles sp resistance to certain chemical insecticides. The involvement ofÂ  Anopheles sp knockdown resistance (kdr) mutationsÂ  asÂ  aÂ  genetic factor in the resistance mechanism, bio-ecological factorsÂ  andÂ  operationalÂ  factors (insecticideÂ  types, application techniques, dose,Â  frequency, time andÂ  mannerÂ  ofÂ  application/intervention)Â  asÂ  theÂ  primaryÂ  cause ofÂ  chemicalÂ  insecticideÂ  resistances. Conclusion: To maintainÂ  thisÂ  programme, we needsÂ  government policies are vectorÂ  controlÂ  integratedÂ  throughÂ  research, assessment, and developmentÂ  ofÂ  vectorÂ  resistance mechanismsÂ  withÂ  insecticides to achieve the goalsÂ  forÂ  globallyÂ  malariaâs free in 2020.